Knowledge and beliefs on vaccines among a sample of Italian pregnant women: results from the NAVIDAD study. (20th November 2019) - Bert, Fabrizio; Olivero, Elena; Rossello, Paola; Gualano, Maria R; Castaldi, Silvana; Damiani, Gianfranco; D'Errico, Marcello M; Di Giovanni, Pamela; Fantini, Maria P; Fabiani, Leila; Gabutti, Giovanni; Loperto, Ilaria; et al.
Abstract: Background: Vaccine hesitancy is an emerging phenomenon in European countries and leads to decreasing trends in infant vaccine coverage. The aim of this study was to analyze the level of confidence and correct awareness about immunizations, which are crucial for the success of vaccination programmes. Methods: As part of the NAVIDAD multicentre study, we examined vaccination confidence and complacency among a sample of 1820 pregnant women from 14 Italian cities. The questionnaire assessed the interviewee's knowledge, beliefs and misconceptions, as well as their socioeconomic status, information sources about vaccines and confidence in the Italian National Healthcare Service. Results: Only 9% of women completely believed to the efficacy, necessity and safety of vaccinations. Almost 20% of them had misconceptions on most of the themes. There was a significant difference in the level of knowledge considering educational level: women with a high educational level have less probability of obtaining a low knowledge score (odds ratio (OR) 0.43 [95% confidence interval (CI) 0.34–0.54]). The level of knowledge was also influenced by the sources of information: women who received information from their general practitioner (GP) and from institutional websites had a significantly lower chance of having misconceptions (OR 0.74 [95% CI 0.58–0.96]; OR 0.59 [95% CI 0.46–0.74]). Finally, the results underlined the influence of trust in healthcare professional information on the likelihood of having misconceptions (OR 0.49 [95% CI 0.27–0.89]). Conclusions: The data suggest the efficacy of GPs and institutional websites as a source of information to contrast misconceptions and underline the importance of confidence in the healthcare system to increase complacency and confidence in vaccines.